2014
DOI: 10.1159/000357619
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Suppresses the Oxidative Response in the Venous Limb of an Arteriovenous Fistula and Enhances the Fistula Blood Flow in Diabetic Rats

Abstract: Objective: The blood flow in the arteriovenous (AV) fistula is significantly reduced in diabetic patients. Statins are known to mediate pleiotropic effects in the vascular endothelium and attenuate inflammatory responses. This study tested the vascular protective effect of rosuvastatin in an experimental model of AV fistula. Methods: One week after the induction of diabetes mellitus (DM) in rats, a fistula was created in the abdominal aorta and inferior vena cava. Rats received placebo or rosuvastatin (15 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Simvastatin had been shown to reduce venous neo-intimal hyperplasia and vascular smooth muscle proliferation by decreasing the expression of vascular endothelial growth factor A (VEGF-A) and matrix metalloproteinase 9 (MMP-9) 14 . Rosuvastatin had been demonstrated to increase the blood flow in the venous limb of AVF in diabetic rats, which was associated with an anti-inflammatory effect and resulting from endothelial function improvement 13 . Atovastatin has been shown to decrease proliferation, migration, and the passage of human smooth muscle cells (HSMC) across a matrix barrier 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin had been shown to reduce venous neo-intimal hyperplasia and vascular smooth muscle proliferation by decreasing the expression of vascular endothelial growth factor A (VEGF-A) and matrix metalloproteinase 9 (MMP-9) 14 . Rosuvastatin had been demonstrated to increase the blood flow in the venous limb of AVF in diabetic rats, which was associated with an anti-inflammatory effect and resulting from endothelial function improvement 13 . Atovastatin has been shown to decrease proliferation, migration, and the passage of human smooth muscle cells (HSMC) across a matrix barrier 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Statins are well known to reduce inflammation and improve endothelial function beyond lowering cholesterol in end stage renal disease patients. In animal studies, statins have been demonstrated to improve blood flow, endothelial function and prevent stenosis of AVF 12 13 14 . Though statins possess these potential protective effects on AVF patency in basic research, several clinical studies have failed to show any association between improved survival of permanent HD access and the prescription of statins 9 15 16 17 .…”
mentioning
confidence: 99%
“…Concentrations of cAMP in the gastric tissues were measured by an ELISA kit (R&D System, USA). The release of superoxide anions from the gastric tissue samples was determined by a luminol-enhanced chemiluminescence chamber (Tohoku Electronic CLA 2100, Sendai, Japan) [ 15 ]. Blood glucose levels were analyzed by the colorimetric assays (ADVIA 1800 Chemistry System, Siemens).…”
Section: Methodsmentioning
confidence: 99%
“…The induction of diabetes was confirmed 48 hours later by measuring the blood sugar concentration using an enzymatic kit (Vital Diagnostics Ltd., Thane, India). Hyperglycemia was defined as a random blood glucose level of more than 250 mg/dL [22].…”
Section: Induction Of Hyperglycemiamentioning
confidence: 99%
“…Immediately before euthanasia, whole blood was collected via a puncture in the inferior vena cava after deep anesthesia. Blood glucose, serum levels of total cholesterol, high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), and triglycerides were analyzed using colorimetric assays (ADVIA 1800 Chemistry System; Siemens, Munich, Germany) as described previously [22].…”
Section: Measurement Of Blood Chemistrymentioning
confidence: 99%